Soil environment reshapes microbiota of laboratory-maintained Collembola during host development - Duleepa Pathiraja; June Wee; Kijong Cho; In-Geol Choi (Environmental Microbiome, 2022)
Abstract Collembola are soil-dwelling arthropods that play a key role in the soil ecosystem. Allonychiurus kimi (Lee) (Collembola: Onychiuridae) was isolated from the natural environment and has been maintained for 20 years under laboratory conditions. Though the morphological and physiological features of A. kimi are being widely used to evaluate the impact of pesticides and heavy metals on the soil ecosystem, variations observed in these features might be on account of its microbiota. However, the microbiota composition of the laboratory-maintained A. kimi is undetermined and how the community structure is changing in response to soil environments or interacting with the soil microbiota are still unknown. In this study, we determined the microbiota of laboratory-maintained A. kimi at both adult and juvenile stages and examined how the microbiota of A. kimi is affected by the microbial community in the soil environments. Chryseobacterium, Pandoraea, Sphingomonas, Escherichia–Shigella, and Acinetobacter were the core microbiota of A. kimi. Exposure of the laboratory-maintained A. kimi to different soil microbial communities drove dynamic shifts in the composition of A. kimi microbiota. Microbial association network analysis suggested that gut microbiota of lab-grown A. kimi was affected by exposing to soil microbial community. This study implies that shifts in the bacterial community of adult A. kimi can be utilized as an indicator to evaluate the soil ecosystem.